Manajemen proyek Sistem Informasi Penggajian Berbasis Web - Edi Setiawan (Universitas Negeri Gorontalo, 2019)
Project management is a strategy that needs to be done in achieving the efficiency and effectiveness of a company. Developments in the era of technology in this period are in line with the development of SMEs engaged in the field of karawo craft services, such as Rumah Karawo. The project planning can be prepared using Work Breakdown Structure (WBS). Project management can also be used to estimate the project acceleration (crasing) at Karawo House. With the preparation of a good project management, it can be estimated the time and cost needed to run the project, so as to minimize cost losses due to the possibility of project overturning. The development of a project management plan carried out using a waterfall.